From a junior coach to the senior ranks: relational transition from a collaborative autoethnographic perspective - Nikander, J. A.; Ryba, T. V. (International Sport Coaching Journal, 2025)
Coaches are key people influencing athletes` careers and their development, especially when athletes approach the junior-to-senior transition. Junior-to-senior mobility also includes transitioning into a new psychosocial environment, including changes in cultural narratives and expectations for both an athlete and their coach. The purpose of this study was to contribute knowledge about a sports coach`s career development and transitions by theorizing a relational co-construction of transitions from the junior level to the senior level. The cultural transition model was used as a conceptual framework to explore the temporality of the first author`s (Jakob) relational transition. To coproduce Jakob`s story, a collaborative autoethnographic approach was utilized. A photo-elicitation method and cyclical interviewing were used to generate the data followed by a thematic narrative analysis. The results indicated that the dominant narratives of elite sport and relation to the athlete shaped Jakob`s subject position, from which he projected his future career as a coach during the transition. Central to relational transition is the understanding that the meaning (re)construction and negotiation of cultural practices occur through interactions with repositioning. The subjective repositioning of both the athlete and the coach can impact the dynamics and outcomes of the transition process.